2000
DOI: 10.1021/jp993444u
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and Intramolecular Effects on the Absorption Spectrum of Betaine-30

Abstract: The effect of solvent electrostatics and solute torsional modes on the absorption spectrum of betaine-30 in acetonitrile is examined. Combined quantum/classical molecular dynamics ground state simulations are used to calculate the electronic absorption spectrum in acetonitrile. The model for betaine-30 includes the electronic degrees of freedom of the π system of the molecule and their interactions with the electric field of the solvent, treating the electronic wave function at the level of Pariser−Parr−Pople … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 47 publications
8
108
0
Order By: Relevance
“…There is little doubt that, as a result of disorder in protic glasses, this specific solvent shift is subject to individual variation, and contributes to the width of IDF. Besides universal and specific solvation, in flexible chromophore structures a geometry modulation can generate additional inhomogeneous broadening [26][27][28]. Unfortunately, there seems to be little experimental evidence for S 1 -S 0 frequency variation as a result of conformational change.…”
Section: Discussionmentioning
confidence: 99%
“…There is little doubt that, as a result of disorder in protic glasses, this specific solvent shift is subject to individual variation, and contributes to the width of IDF. Besides universal and specific solvation, in flexible chromophore structures a geometry modulation can generate additional inhomogeneous broadening [26][27][28]. Unfortunately, there seems to be little experimental evidence for S 1 -S 0 frequency variation as a result of conformational change.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an amino wag angle and single bond and double bond twist angles were defined for JM as (180 À D (2, 1, 8, 3))/2, D (12,13,14,15), and D (13, 14, 15, 17), respectively. As in PNA, the amino wag angle is strongly correlated to the hybridization of the amino nitrogen; a decrease in this angle signifies the evolution from sp 3 to sp 2 hybridization, sp 2 hybridization being associated with the zwitterionic basis state.…”
Section: Ground and Excited State Potential Energy Surfaces Of Jmmentioning
confidence: 99%
“…Gao and Alhambra [9] obtained similar results for the some of the same molecules considered in [6] using a hybrid quantum mechanical and molecular mechanics methodology. Recent work on the betaine-30 dye molecule [11,12] has focused on electronic effects related to the torsional coordinate between its p conjugated rings, and the importance of this contribution as a function of media polarity; the general conclusion was that the potential along the torsional coordinate has a much larger curvature in the isolated molecule than in solution. Farztdinov et al [13] used semiempirical methods to explore the excited state potential energy surface of p-nitroaniline as a function of solvent.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we employed a MS-EVB approach to model the quantum nature of proton, observed through its delocalization, together with MD techniques which allowed us to monitor the trajectory of all particles in time. Although this combined methodology has been widely used to study chemical reactivity in solution, [11,14,17,19,26,[43][44][45][46][47][48][49][50][51] we will describe the most important details of the methodology below.…”
Section: Methodsmentioning
confidence: 99%